IMPROVEMENT AND CHALLENGES IN QUALITY OF EDUCATION OF PRIMARY AND SECONDARY SCHOOLS IN LALITPUR DISTRICT: ललितपुर जनपद में प्राथमिक एवं माध्यमिक विद्यालयों की शिक्षा की गुणवत्ता में सुधार एवं चुनौतियां - Yadav, NK Sharma; Kumar, Rajesh (International Journal of Research -GRANTHAALAYAH, 2021)
English: The research study area presented under the title "Improvement and quality of education in primary and secondary school in Lalitpur district". The global economy of the 21st century can thrive in an environment that is based on creativity and imagination, critical thinking and problem-solving skills. There is a strong positive relationship between empirical analysis, economic progress and education. According to the 2011 census in India, school-aged children between the ages of 6-14 years have a huge population of 30.5 million, which is about 25 percent of the total population. The goal of development is to focus on the quality of primary and secondary education by 2030. The Prime Minister of India, Shri Narendra Modi has said in one of his speeches (Mann Ki Baat) about the importance of quality. "Till now the focus of the government was the spread of education across the country but now the time has come to focus on the quality of education Should be given and now attention should be given to schooling knowledge.” In this regard, Human Resources Minister Prakash Javadekar has said that" Top priority to improve the quality of education in the country, primary and secondary education facing challenges, 16 percent of 19.67 crore children in 14.5 lakh primary schools under the Sarva Shiksha Abhiyan and 16 percent of the schooling at the secondary level. Has decreased. Thus, to improve the quality of education, skill technical, innovation training technology, information technology employment, education development mission and vocational employment education are urgently needed. Hindi: प्रस्तुत शोध अध्ययन क्षेत्र ‘‘ललितपुर जनपद में प्राथमिक एवं माध्यमिक विद्यालय में शिक्षा की गुणवत्ता में सुधार एवं चुनौतियाँ ‘‘ शीर्षक के अन्तर्गत अध्ययन किया है। 21 वीं शताब्दी की वैश्विक अर्थव्यवस्था ऐसे वातावरण की उन्नति कर जो रचनात्मकता एवं काल्पनिकता , विवेचनात्मक सोच और समस्या के समाधान से सम्बन्धित कौशल पर आधारित है। अनुभवमूलक विश्लेषण , आर्थिक उन्नति एवं शिक्षा के मध्य सुदृढ़ सकारात्मक सम्बन्ध होते है। भारत में 2011 की जनगणना के अनुसार स्कूल जाने वाले बच्चों की आयु 6-14 वर्ष के मध्य 30.5 करोड़ विशाल जनसंख्या है जो कुल जनसंख्या का लगभग 25 प्रतिशत है। विकास का लक्ष्य 2030 तक प्राथमिक एवं माध्यमिक शिक्षा की गुणवत्ता पर ध्यान देने की आवश्यकता है। भारत के प्रधानमंत्री श्री नरेन्द्र मोदी जी ने अपने एक एक उद्बोधन (मन की बात) में गुणवत्ता के महत्व में कहा है ‘‘ अब तक सरकार का ध्यान देश भर में शिक्षा का प्रसार था किन्तु अब वक्त आ गया है कि ध्यान शिक्षा की गुणवत्ता पर दिया जाय और अब स्कूलिंग ज्ञान पर ध्यान देना चाहिएं।‘‘ इस सम्बन्ध में मानव संसाधन मंत्री प्रकाश जावडे़कर ने कहा है कि ‘‘ देश में शिक्षा की गुणवत्ता में सुधार की सर्वोच्च प्राथमिकता, चुनौतियों का सामना करके प्राथमिक एवं माध्यमिक शिक्षा, सर्वशिक्षा अभियान के अन्तर्गत 14.5 लाख प्राथमिक विद्यालय में 19.67 करोड़ बच्चों की प्राथमिक स्तर पर 16 प्रतिशत तथा माध्यमिक स्तर पर 32 प्रतिशत बच्चों की स्कूली शिक्षा में कमी हुई है। इस प्रकार शिक्षा की गुणवत्ता को बेहतर बनाने के लिए कौशल तकनीकी, नवाचार प्रशिक्षण तकनीकी, सूचना तकनीकी रोजगार , शिक्षा विकास मिशन तथा व्यावसायिक रोजगार परक शिक्षा की अति आवश्यकता है।